(3OjhGf TPhQ GdPgHs - (3GHf GQaY QGSg GdCfOdSj GdLjGfj, GHf GQaY QGSg GdCfOdSj GdLjGfj,J (B593 (3g` s ((3Shjai Hf CMeO GdYOhi s)
(3ChdgG (B:s
( (3bGajI GdCda (B) (3EPG KdK GdeQjN HGdRgQI GeQD hbGQf HGdHOQ GdefjQ PcGA s
(3BNQgG (B:s
( (3ef bGajI GdjGA(B) (3hGdG adG JQJY HgG ai QhVI bO GeJdCJ ddQGFOjf CaGYjG s
(3OjhGf eQJH Ydi GdMQha GdgLGFjI ai GdUfYI GdEdgjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B26s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B496 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B908 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B65 s
Keywords: (3GdcjejGA h GdWHjYjGJs